All cause 30 readmission in patients with history of sudden cardiac arrest. (25th November 2020) - Mastoris, I; Acharya, P; Haglund, N; Sauer, A; Shah, Z
Abstract: Background: Sudden cardiac arrest (SCA) remains a significant cause of morbidity and mortality. Current evidence on readmission rates and causes after SCA are scarce. Purpose: To describe patient characteristics, predictors of readmission and outcomes patients with history of sudden cardiac arrest and 30-day readmission Methods: We analyzed the National Readmission Database for years 2016 and 2017 to identify all patients with initial diagnosis of SCA and 30 days readmission after the initial event. We analyzed baseline characteristics and looked into predictors, outcomes and diagnoses of re-admission. Results: We identified 79, 844 patients with an initial diagnosis of SCA that were discharged alive after index admission. Of those 14, 387 (18.01%) had one readmission and 3, 978 (4.99%) had more than one readmission. The mean age was 64 years and 41.3% were females. Hypertension, dyslipidemia, diabetes, CAD, CHF and CKD were present in 76.5%, 42.4%, 46.3%, 50.4%, 62.3% and 43.5% respectively. Overall mortality was 9.1% and length of stay 7.8 days. (Table 1). Congestive heart failure was the predominant diagnosis for readmission (Figure). Female sex (HR=0.93; p=0.004) was the only independent risk factor for all cause readmission. Conclusions: Patients with history of SCA that have a 30-day readmission have significantly more comorbidities and length of day. Congestive heart failure is the predominant diagnosis for readmission Funding Acknowledgement: Type of funding source: None